From Farms to Markets: Gram-Negative Bacteria Resistant to Third-Generation Cephalosporins in Fruits and Vegetables in a Region of North Africa - Mesbah Zekar, Ferielle; Granier, Sophie A.; Marault, Muriel; Yaici, Lydia; Gassilloud, Benoit; Manceau, Charles; Touati, Abdelaziz; Millemann, Yves (Frontiers in Microbiology, 2017)
The role of food in human exposure to antimicrobial-resistant bacteria is a growing food safety issue. The contribution of fruits and vegetables eaten raw to this exposure is still unclear. The evaluation of contamination levels of fruits, vegetables and the agricultural environment by third-generation cephalosporin (3GC)-resistant Gram-negative bacteria was performed by analysing 491 samples of fruits and vegetables collected from 5 markets and 7 farms in Bejaia area, north-eastern Mediterranean coast of Algeria. 90 soil samples and 45 irrigation water samples were also sampled in farms in order to assess them as potential inoculum sources. All samples were investigated at the same time on ceftazidime-containing selective media for 3GC-resistant Gram-negative bacteria detection and on Haektoen media, for Salmonella spp presence. The bacteria isolated (n=30) from fruits and vegetables, soil and irrigation water collected in the farms were almost all non-fermenting bacterial species (Stenotrophomonas, Acinetobacter, Pseudomonas, Ochrobactrum) except one strain of Enterobacter cloacae and two strains of Citrobacter murliniae, isolated on one cucumber and two tomato samples in the same farm. Greater diversity in bacterial species and antimicrobial resistance profiles was observed at markets: Enterobacteriaceae (n=41) were as strongly represented as non-fermenting bacteria (n=37). Among Enterobacteriaceae, Enterobacter cloacae (n=21) and Klebsiella pneumoniae (n=13) were the most common isolates. Most of the Klebsiella pneumoniae isolates were extended-spectrum beta-lactamase (ESBL) producers (n=11). No Salmonella spp. was recovered in any sample. This study showed that fruits and vegetables including those which may be eaten up raw constitute a reservoir of 3GC-resistant Gram-negative bacteria and multi-drug resistant-bacteria in general that can be transferred to humans through food. The general public should be informed of this hazard for health in order to encourage good domestic hygiene practices. In addition, further investigation is needed throughout the production chain to enrol professionals in actions to reduce this contamination.